Hubungan Asupan Natrium dengan Perubahan Tekanan Darah pada Pasien Gagal Ginjal Kronik Rawat Jalan yang Menjalani Hemodialisis di RSUD Kabupaten Sukoharjo - Fatmawati, Inna; , Endang Nur W, S.St., M.Si.Med; , Tuti Rahmawati, S.Gz.,M.Si (2015)
Introduction: Chronic renal failure is a failure in renal function that progresses slowly resulting accumulation of residual metabolites. Hemodialysis therapy can maintain a stable kidney function so their health condition does not get worse. Chronic renal failure patients with hemodialysis should pay attention to proper diet (especially their sodium intake) to controll blood pressure and edema. Objective: This study aimed to determine the relationship between sodium intake and changes in blood pressure in chronic renal failure with hemodialysis outpatients at district hospital of Sukoharjo. Research method: This research used observational with cross-sectional design. The research subject were chronic renal failure with hemodialysis outpatients at district hospital of Sukoharjo. Sampling technique used consecutive sampling. Blood pressure data were obtained from medical record, while sodium intake data were obtained through interview using a semi-quantitative FFQ method. Statistical analyzis of relationship between sodium intake and changes in blood pressure used Spearman's Rank tests. Results: The univariate results indicated that 80,6% patients had sufficient sodium intake, 100% patients had change in systolic blood pressure and 74,2% patients had change in diastolic blood pressure. The bivariate results indicated that there was no relationship between sodium intake and change in systolic blood pressure (p = 0.083) and change in diastolic blood pressure (p = 0.414). Conclusion : There was no relationship between sodium intake and changes in systolic and diastolic blood pressure in chronic renal failure with hemodialysis outpatients at district hospital of Sukoharjo. Suggestion: Futher researches are needed in patients who do not get antihypertension class Angiotensin Converting Enzyme inhibitor (ACE inhibitor) drugs and take into account other factors such as obesity, physical activity, smoking habits, alcohol consumption and stress.